Key Audit Matters in Financial Reporting and Auditing: A Bibliometric Analysis - Judijanto, Loso; Deswin, Yendri (The Es Accounting And Finance, 2026)
This study aims to map the intellectual structure and research trends of Key Audit Matters (KAM) in financial reporting and auditing through a comprehensive bibliometric analysis. Using data retrieved from Scopus and analyzed with VOSviewer, the study examines publication patterns, keyword co-occurrence, and thematic evolution within the KAM literature. The findings reveal that KAM has become a central topic in auditing research, closely associated with audit reporting, financial reporting quality, and information asymmetry. The analysis identifies several major research clusters, including audit disclosure practices, regulatory frameworks, and the economic consequences of KAM. Temporal analysis indicates a shift from early conceptual and standard-focused studies toward more recent empirical investigations addressing practical issues such as audit report lag, audit firm behavior, and the impact of external factors like the COVID-19 pandemic. Additionally, the study highlights the growing geographical diversity of KAM research, reflecting its global relevance across different regulatory environments. Despite the maturity of core themes, emerging topics remain underexplored, offering opportunities for future research. This study contributes to the literature by providing a systematic overview of KAM research and offers insights for academics, practitioners, and policymakers in enhancing audit transparency and financial reporting quality.